CFD analysis of CO2 absorption in a microporous tube-in-tube microchannel reactor with a novel gas-liquid mass transfer model. (April 2020) - Li, Wen-Ling; Wang, Jian-Hong; Lu, Ya-Cong; Shao, Lei; Chu, Guang-Wen; Xiang, Yang
Highlights: A novel mass transfer model was proposed based on the eddy cell model. 3D simulation of CO2 absorption by H2 O in MTMCR was carried out under various conditions. The numerical results using eddy cell model with the coefficient of 0.4 and novel mass transfer model were discussed in detail. The simulated results with the novel mass transfer model were in good agreement with the experimental data in a wide range of operations. Abstract: Due to the greenhouse effect, new technologies of CO2 capture attract wide attention. In this paper, computational fluid dynamics (CFD) was employed to simulate the absorption of CO2 in a microporous tube-in-tube microchannel reactor (MTMCR). Based on the eddy cell model, a novel gas-liquid mass transfer model considering the surface work was proposed and the simulated results of volumetric mass transfer coefficient agreed well with the published experimental data. In the lower turbulence range, the deviations between experimental data and predictions of kl a using eddy cell model are over ± 40%. Meanwhile, results from the modified eddy cell model agree well with experimental data within ±10% deviation in a wide range of operating conditions. The novel gas-liquid mass transfer model could benefit for understanding the mass transfer mechanism and improving the mass transfer performance in reactors.